Effects of alfentanil or fentanyl added to propofol for sedation in colonoscopy on cognitive functions: Randomized controlled trial - Doğanay, Güler; Ekmekçi, Perihan; Kazbek, Baturay Kansu; Yılmaz, Hakan; Erkan, Gülbanu; Tüzüner, Filiz (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: To assess the effect of propofol supplemented with alfentanil or fentanyl on cognitive functions for sedation during elective colonoscopy. Materials and Methods: Patients (n=150, 18-65 years old, American Society of Anesthesiologists risk group I-III) scheduled undergo elective colonoscopy were included. They were randomized into three groups using the closed envelope methodpropofol-alfentanil (Group A), propofol-fentanyl (Group F), and propofol only (Group P).Group A patients were given an alfentanil (10 mcg/kg)-supplemented propofol bolus infusion and 5 mcg/kg alfentanil when necessary. Group F patients were given fentanyl (1 mcg/kg)-supplemented propofol and 0.5 mcg/kg fentanyl when necessary. Group P patients were given 1 mg/kg propofol and 0.5 mg/kg propofol when necessary. Vital signs, depth of sedation, recovery parameters, and patient and endoscopist satisfaction were recorded. Trieger dot test (TDT) and Digit Symbol Substitution Test (DSST) were performed post procedure. Results: Demographic data were similar among all patients in the groups. Bispectral index values were lower in Group P (p Conclusions: Compared with propofol-alfentanil and propofol-fentanyl, propofol alone is associated with an increased incidence of apnea, drug consumption, and reported pain. Propofol-alfentanil has a less negative effect on cognitive functions than propofol alone or propofol-fentanyl.